The application of auxetic material for protective sports apparel - Moroney, C.; Alderson, A.; Allen, T.; Sanami, M.; Venkatraman, P. (Proceedings, 2018)
Current research of auxetic materials highlights its potential as personal protective equipment for sports apparel with enhanced properties such as conformability, superior energy absorption and reduced thickness. In contrast, commercially available protective materials have proven to be problematic in that they inhibit movement, breathability, wicking and that molded pads are prone to saddling. Foam components are embedded within personal protective equipment for sports apparel, where protective material is positioned at regions of the body frequently exposed to injury of the soft tissue through collision, falls or hard impact. At present, the impact resistance of auxetic open cell polyurethane foam and some additively manufactured auxetic structures have been established, and processes for manufacturing curved auxetic materials as well as molding methods have been developed. Despite this, auxetic materials have not yet been applied as personal protective equipment for sports apparel in current research. This paper argues that there is scope to investigate auxetic materials potential for enhanced wearer functionality through properties of synclastic curvature and biaxial expansion.